Hippocampal neuroligin-2 links early-life stress with impaired social recognition and increased aggression in adult mice. (May 2015) - Kohl, Christine; Wang, Xiao-Dong; Grosse, Jocelyn; Fournier, Céline; Harbich, Daniela; Westerholz, Sören; Li, Ji-Tao; Bacq, Alexandre; Sippel, Claudia; Hausch, Felix; Sandi, Carmen; Schmidt, Mathias V.
Highlights: Early life stress results in impaired social behavior and increased aggression. Early life stress increases hippocampal neuroligin-2 expression. Increasing neuroligin-2 expression mimics the stress-induced phenotype. Knockdown of neuroligin-2 ameliorates stress-induced deficits. Summary: Early-life stress is a key risk factor for the development of neuropsychiatric disorders later in life. Neuronal cell adhesion molecules have been strongly implicated in the pathophysiology of psychiatric disorders and in modulating social behaviors associated with these diseases. Neuroligin-2 is a synaptic cell adhesion molecule, located at the postsynaptic membrane of inhibitory GABAergic synapses, and is involved in synaptic stabilization and maturation. Alterations in neuroligin-2 expression have previously been associated with changes in social behavior linked to psychiatric disorders, including schizophrenia and autism. In this study, we show that early-life stress, induced by limited nesting and bedding material, leads to impaired social recognition and increased aggression in adult mice, accompanied by increased expression levels of hippocampal neuroligin-2. Viral overexpression of hippocampal neuroligin-2 in adulthood mimics early-life stress-induced alterations in social behavior and social cognition. Moreover, viral knockdown of neuroligin-2 in the adult hippocampus attenuates the early-life stress-induced behavioral changes. Our results highlight the importance of neuroligin-2 in mediating early-life stress effects on social behavior and social cognition and its promising role as a novel therapeutic target for neuropsychiatric disorders.